2005
DOI: 10.1080/03014460500049915
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns and time allocation during pregnancy: A longitudinal study of British women

Abstract: Low-risk pregnancy has a differential impact on occupational, recreational and domestic domains. Economies in energy expenditure appear to be made in occupational and recreational activity while domestic activities are largely maintained during pregnancy. Changes in physical activity may be influenced more by the type of activity rather than the intensity of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 13 publications
7
50
0
3
Order By: Relevance
“…The study participants were of low-risk pregnancy, retention of the sample was high and the final sample included those without any medical complications. Comparisons of the study sample with published data demonstrated that they were broadly representative of British women in terms of habitual activity, socioeconomic status and birth outcomes (Clarke et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The study participants were of low-risk pregnancy, retention of the sample was high and the final sample included those without any medical complications. Comparisons of the study sample with published data demonstrated that they were broadly representative of British women in terms of habitual activity, socioeconomic status and birth outcomes (Clarke et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Continuous monitoring of day and night-time activity was included to examine change in sleep patterns during pregnancy (Clarke et al, 2005). Women were instructed to go about their normal daily routine and only remove the actiwatch during periods of bathing or watersports.…”
Section: Methodsmentioning
confidence: 99%
“…The pregnancy PA patterns have so far been investigated through questionnaires (Lof and Forsum, 2006) or interviews (Clarke et al, 2005;Rousham et al, 2006;Borodulin et al, 2008). However, the reliability and validity of all selfreported methods is limited because of misreporting or miscoding of activities, inaccurate estimation of activity intensity or duration and differences in body mass.…”
Section: Introductionmentioning
confidence: 99%
“…The energy cost of DIT seems to be unaltered (Nagy and King, 1984;Poppitt et al, 1993;Spaaij et al, 1994;Bronstein et al, 1995;Piers et al, 1995;Prentice et al, 1996) or even reduced (Contaldo et al, 1987;Illingworth et al, 1987;KoppHoolihan et al, 1999). The energy cost attributed to PA is generally low (Lawrence and Whitehead, 1988;Butte et al, 2004;Clarke et al, 2005;Lof and Forsum, 2006;Rousham et al, 2006) and tends to decrease as pregnancy advances (Lawrence et al, 1985;van Raaij et al, 1987;Singh et al, 1989;Heini et al, 1991;Forsum et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of physical activity patterns during pregnancy show a low prevalence of recommended activity levels 15,16,17 , as well as a decline of leisure physical activity/sports/exercise and occupational activity across gestation 6,15,16,18,19,20,21,22,23,24 . Even so, there is some evidence that household and childcare activities are maintained over the course of pregnancy 18,22 or increase in the third trimester 23 .…”
mentioning
confidence: 99%